HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KEMANDIRIAN PERSONAL HYGIENE ANAK TUNAGRAHITA DI SLB TUNAS MULYA KELURAHAN SEMEMI KECAMATAN BENOWO - Alfita Sari, Oktavia Alfita Sari; Heris Santy, Wesiana (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2017)
children with mental retardation are remarkable because they have limitations compared to normal children, both in terms of physical, intellectual, social, economic, but still can be trained to be independent. To be able to master the ability of good personal hygiene is needed supports from the Parents. This study aims to determine the relationship of family support with personal hygiene level of independence of children with intellectual challenges in SLB Tunas Mulya Kelurahan Sememi kecamatan Benowo. The research design was qualitative analytic using cross sectional approach. The population were 27 parents with simple random sampling method where it gets 25 parents. Family support dependent variable and the independent variable degree of independence tunagrahita personal hygiene. Collecting data using questionnaires and research analysis using Rank Spearman with the correlation level α = 0.05. The results of the 25 respondents obtained the majority (52%) of respondents give good support, nearly half (44%) of respondents are quite independent, the test results Spearman Rank Correlation P Value = 0,030 so that ρ <α then H0 is rejected means that there is a relationship between support families with tunagrahita children’s personal hygiene level SLB Tunas Mulya Kelurahan Sememi Kecamatan Benowo. The conclusion of this research was good supports make children with mental retardation independent enough, so it is suggested to well support in order to make the children with mental retardation independent.